Chalcogen bonding mediates the formation of supramolecular helices of azapeptides in crystals. Issue 29 (12th July 2021) - Shi, Di; Cao, Jinlian; Weng, Peimin; Yan, Xiaosheng; Li, Zhao; Jiang, Yun-Bao
Abstract : Supramolecular M - and P -helices are formed via intermolecular S⋯S and S⋯O chalcogen bonding of alanine-based azapeptides containing a β-turn structure and equipped with a thiophene group at the N - or C -terminus, respectively. Abstract : To explore whether chalcogen bonding was able to drive the formation of supramolecular helices, alanine-based azapeptides containing a β-turn structure, with a thiophene group, respectively, incorporated in the N - or C -terminus, were employed as helical building blocks. While the former derivative formed a supramolecular M -helix via intermolecular S⋯S chalcogen bonding in crystals, the latter formed P -helix via intermolecular S⋯O chalcogen bonding.